2018
DOI: 10.1039/c8ra01736k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical performance of poly(ether ether ketone)/zinc oxide nanocomposites to provide promising biomaterials for trauma and orthopedic implants

Abstract: Poly(ether ether ketone)/zinc oxide (PEEK/ZnO) composites were manufactured by using the injection molding technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
(39 reference statements)
1
22
1
1
Order By: Relevance
“…Regarding the crystalline structure of the composite materials, the presence of ZnO and PEEK with its characteristic hexagonal wurtzite and orthorhombic unit cell [ 36 ], respectively, was evidenced in the diffraction patterns ( Figure 2 ). The narrower peaks in the composites in comparison with those of pure PEEK could be indicative of a decrease in the spherulite’s size promoted by the presence of ZnO, as observed by Jiang et al [ 37 ], as well as a decrease in the crystal domains distribution. The slight shift to a smaller 2θ angle in the presence of ZnO could be indicative of a partial disruption of the crystalline structure of PEEK, provoked by the nanostructures, increasing the d -space in the crystalline lattice.…”
Section: Discussionmentioning
confidence: 51%
“…Regarding the crystalline structure of the composite materials, the presence of ZnO and PEEK with its characteristic hexagonal wurtzite and orthorhombic unit cell [ 36 ], respectively, was evidenced in the diffraction patterns ( Figure 2 ). The narrower peaks in the composites in comparison with those of pure PEEK could be indicative of a decrease in the spherulite’s size promoted by the presence of ZnO, as observed by Jiang et al [ 37 ], as well as a decrease in the crystal domains distribution. The slight shift to a smaller 2θ angle in the presence of ZnO could be indicative of a partial disruption of the crystalline structure of PEEK, provoked by the nanostructures, increasing the d -space in the crystalline lattice.…”
Section: Discussionmentioning
confidence: 51%
“…No other reflections could be observed except for those corresponding to perovskite‐type and PEEK phases, indicating the chemical stability between the two phases as expected. The intensity of PEEK phase decreases as the amount of LNT filler increases, which may imply that the addition of ceramic particles can change the spherulite's size of PEEK as reported …”
Section: Resultsmentioning
confidence: 91%
“…The antibacterial property enhanced with the increase in the ZnO content, and the best antibacterial property was obtained at 7.5 wt% of the modified nanoparticles. Hao et al (2018) synthesized PEEK/ZnO nanocomposites by conventional melting blending and compression molding and studied the properties of the composites. The results showed that the mechanical properties and thermal stability of the composites were significantly improved and the composites had good cellular compatibility.…”
Section: Other Peek Compositesmentioning
confidence: 99%